Αξιολόγηση σχημάτων κρυπτογράφησης με δυνατότητα αναζήτησης - Μπάκας, Αλέξανδρος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Εφαρμοσμένων Μαθηματικών και Φυσικών Επιστημών, 2017)
The present text aims to demonstrate cutting-edge technologies, such as cloud computing, and then to show how a simple day-to-day user can use these technologies without making compromises in terms of security and privacy. More specifically, we are studying systems that allow us to store files in the cloud in such a way that the provider learns nothing about the stored files. This gives the user a sense of security when he places files in the cloud. More precisely, descriptions of such symmetric and public key systems are given, where the main scenario is a user uploading encrypted files to the cloud and then through a search token, searches in the encrypted data base for those that contain a keyword associated with the search token. We are examining both static searchable encryption schemes , which are easier to implement, but less practical, as we want most databases to be able to be updated, and dynamics, which, although more practical, leak much more information. We then see how such public key systems are associated with other encryption techniques, such as functional encryption and identity based encryption. These schemes are evaluated on the basis of some parameters, such as efficiency, safety and running time. The text ends with a literary section on privacy, which is a global issue after the outbreak of terrorist attacks lately.